Energy security along the new silk road : energy law and geopolitics in Central Asia / Anatole Boute. - Boute, Anatole (Cambridge studies on environment, energy and natural resources governance., 2019)
Guaranteeing energy security is one of the most complex challenges of energy law and policy. Energy insecurity threatens economic development, social peace and stability. This book focuses on energy security in the strategically important region of Central Asia. The region holds huge energy reserves, but its energy systems are highly inefficient and unreliable, and thus require urgent reform. However, endemic corruption, discrimination and the strong centralization of power have so far blocked initiatives to reorganize energy supply. The case of Central Asia is uniquely relevant for understanding the informal constraints on energy law and policy. In addition, Central Asian energy insecurity illustrates the impact of geopolitics on the regulation of energy markets. The region is strategically located in Russia's sphere of influence and along China's New Silk Road. Its energy situation highlights the complex interactions amongst energy law, geopolitics and institutions.